Finance in Lower Income Countries : An Empirical Exploration - Gupta, Poonam; Detragiache, Enrica; Tressel, Thierry (Washington, D.C. : International Monetary Fund, 2005)
This paper considers how a comprehensive set of factors relates to financial sector performance in low-income countries (LICs). It finds that corruption and inflation are associated with a shallower and less efficient financial system, while legal origin and characteristics of the supervisory and regulatory framework have no significant relationship with performance. Moreover, better contract enforcement and information about borrowers are associated with more private sector credit. Some results are surprising. Countries with more foreign bank penetration seem to have shallower and not necessarily more efficient financial sectors, while a larger presence of state-owned banks is correlated with more bank deposits and lower overhead costs, even after controlling for market size and concentration. Although these relationships are robust, more research is needed to ascertain the direction of causality and identify channels of transmission before deriving policy implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet